Religion in the Andes to Canta at the end oflnca and Early Colonial Times - Cajavilca Navarro, Luis (2011)
The dergy dedicared ro serving great rcligious ccnrers and dedicated to serving [he rdigion of rhe ayIlu ín Canta, established between them a sysrem which kepr up a precarious balance through the deploymenr of rhe expansión force of (he Incas, artenuated by rhe use of sweerened domain merhods such as win hearts of polirícal leaders, as wel! as of priests by mcans of gifls, delivery ofcamels ro be sacrificed ro rhe gods: «Wa-Kon and Tícllahuacho, Urau, Cerro Mancos and Nevado de la Viuda» and the assignrnenr of personal privilegc to dignitaries ar dlffercnt levels. Bur however (he concurrence of the [\'10 pricsrly groups wirhin system, insrability was always presen( in (he relationship berween thern, so rnuch so gods and priests can deal almost as parallel systerns, on whích would top up these new c1ergy of colonial origino